Influence of Plasmodium falciparum Calcium-Dependent Protein Kinase 5 (PfCDPK5) on the Late Schizont Stage Phosphoproteome - Blomqvist, Karin (mSphere, 2020)
Protein kinases are important mediators of signal transduction in cellular pathways, and calcium-dependent protein kinases (CDPKs) compose a unique class of calcium-dependent kinases present in plants and apicomplexans, including Plasmodium parasites, the causative agents of malaria. During the asexual stage of infection, the human malaria parasite Plasmodium falciparum grows inside red blood cells, and P. falciparum calcium-dependent protein kinase 5 (PfCDPK5) is required for egress from the host cell. In this paper, we characterize the late-schizont-stage P. falciparum phosphoproteome by performing large-scale phosphoproteomic profiling on tightly synchronized parasites just prior to egress, identifying 2,704 phosphorylation sites on 919 proteins. Using a conditional knockdown of PfCDPK5, we identify 58 phosphorylation sites on 50 proteins with significant reduction in levels of PfCDPK5-deficient parasites. Furthermore, gene ontology analysis of the identified proteins reveals enrichment in transmembrane- and membrane-associated proteins and in proteins associated with transport activity. Among the identified proteins is PfNPT1, a member of the apicomplexan-specific novel putative transporter (NPT) family of proteins. We show that PfNPT1 is a potential substrate of PfCDPK5 and that PfNPT1 localizes to the parasite plasma membrane. Importantly, P. falciparum egress relies on many proteins unique to Apicomplexa that are therefore attractive targets for antimalarial therapeutics. IMPORTANCE The malaria parasite Plasmodium falciparum is a major cause of morbidity and mortality globally. The P. falciparum parasite proliferates inside red blood cells during the blood stage of infection, and egress from the red blood cell is critical for parasite survival. P. falciparum calcium-dependent protein kinase 5 (PfCDPK5) is essential for egress; parasites deficient in PfCDPK5 remain trapped inside their host cells. We have used a label-free quantitative mass spectrometry approach to identify the phosphoproteome of schizont-stage parasites just prior to egress and identify 50 proteins that display a significant reduction in phosphorylation in PfCDPK5-deficient parasites. We show that a member of the Apicomplexan-specific transport protein family, PfNPT1 is a potential substrate of PfCDPK5 and is localized to the parasite plasma membrane. P. falciparum egress requires several proteins not present in human cells, thus making this pathway an ideal target for new therapeutics.